Modernizers and Traditionalists in Postwar Hamilton, Ontario: The Fate of a Farmers' Market, 1945-1965 - Robinson, Danielle (Urban History Review / Revue d'histoire urbaine, 2007)
Between 1945 and 1965, the Hamilton Farmers' Market was hailed as both an irreplaceable cultural and historical gem, and condemned as an antiquated institution not worth the land it occupied. The market debates occurred in the midst of post-World War II suburban sprawl, fuelled and facilitated by the automobile. This change in the postwar landscape accommodated the rise of powerful modernist ideology as well as a traditionalist response. Debates over the market's fate touched on reducing, relocating, or eliminating the market completely. The chosen solution—constructing a parking ramp on the market site, and housing the market on the ground level of the structure—was implemented by October 1960. This was a victory for the city's modernizers, and foreshadowed the more extensive urban renewal efforts that dominated regional politics in the late 1960s and 1970s.